Fuzzy stock selection using a new fuzzy ranking and weighting algorithm - Tiryaki, F; Ahlatcioglu, M (ELSEVIER SCIENCE INC, 2005)
This paper proposes a new method for group decision making in fuzzy environment and demonstrates the usefulness of fuzzy methodology in financial problems. In here it is accomplished by making some modification of Chen's method [Fuzzy Sets and Systems, 118 (2001) 65-73] and it is shown how our method can be used for stocks selection on ISE (Istanbul Stock Exchange). The rating of each stock and the weight of each criterion are described by linguistic terms expressed in triangular fuzzy numbers. And also Chen's two methods [Fuzzy Sets and Systems, 114 (2000) 1-9; Fuzzy Sets and Systems, 118 (2001) 65-73] we used only give the ranking order of stocks to the investors or decision maker (DM)s. Whereas, it's evident that DMs would like to know not only the ranking order of stocks, but also at which proportion they would invest in a particular stock. So, our proposed model provides both ranking and weighting information to the investors. (c) 2004 Elsevier Inc. All rights reserved.
Keywords: fuzzy MCDM; linguistic variables; triangular fuzzy number; portfolio selection; finance; GROUP DECISION-MAKING; INFORMATION; Mathematics